ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Konsumen Waroeng Steak & Shake Cabang Jl. Sriwijaya 11 Semarang) - Kurniasari, Nova Dhita; Santosa, Suryono Budi (Diponegoro Journal of Management, 2013)
Research aims to know whether price, quality of product, and service quality influence the decision purchase consumers Waroeng Steak & Shake and analyzing factor the most dominant ineffecting decision purchase consumers Waroeng Steak & Shake in Semarang.The population in this research is the consumer of consumers Waroeng Steak & Shake. The sample  is  taken  from  100  respondents  with  the  Non-Probability  Sampling  technique  withAccidental Sampling approach that the determination of the sample is accidentally taken—those who meet the researcher can be a sample if deemed appropriate.The  result  showed  price,  quality  of  product,  and  service  quality  have  positive  and significant impact to the purchasing decision. Based on the statistic data analysis, the indicators in this research is valid and the variable is reliable. In the classical testing assumption, the regressionmodel is free multicollonierity, the heteroscedasticity does not occur, and normal distribution. Order individually from each of the most influential variable is the variable quality of product andservice quality, while the most influential variables are low is the price. The suggestion from the writer to increase the consumer's purchasing decision can be carried out by means of competitivepricing, increasing the diversity of products, and improve the quality of his service. Waroeng Steak& Shake the need to preserve the elements which have been rated good (price, quality of product, and service quality) by the customer as well as the need to fix the things that are lacking (promotion).